LITERATURE REVIEW: LITERASI SAINS SISWA PADA MATERI KIMIA - Nurul Siam, Aulia (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2024)
This research focuses on analyzing research trends regarding students' scientific literacy in chemistry material. This research contains an analytical study of the number of articles published on chemistry education with research in Indonesia in 2018-2023. The study was conducted on 16 journal articles. The analysis step begins with reading the abstract and data reduction and drawing data conclusions based on the research instruments used. Research topics include chemical material analysis, number of publications, research subjects, and research method trends. Among these publications, the most dominant research designs are quantitative and R&D research. Based on these findings, several recommendations were found for further research to enrich knowledge and provide useful results. The recommended type of research is quantitative research and R&D methods to analyze scientific literacy. In connection with the findings of this research, recommendations for future research are to base the topic of scientific literacy as the main focus by choosing more appropriate research methods.